Noções de tratamento da informação por meio de jogos nos anos iniciais do ensino fundamental - Rosa, Cátia Pereira da (2016)
This research is limited to the field of mathematics education and is justified by the need to reflect on the theoretical and methodological aspects concerning the use of games in the educational field as well as on their contributions to the teaching content belonging to that area. Therefore, this study aimed to verify the use of games can contribute to the teachinglearning process of content related to the Information Treatment block in the early years of elementary school. The methodology for the research is qualitative in nature, seeking to understand the phenomena involved in educational practice. The selected method of investigation was the type case study, investigating students in the early years of elementary school under situations of mathematical games to observe and answer the main question of research. The data analysis has to underwrote on the conceptions of CulturalHistorical theory and Registers of Semiotics Representation theory, along with considerations of authors who talk about games and themes on information processing. As a result of the information collected can be noticed mainly two interrelated moments that occurred important learning. First, the analysis of developed game situations highlight the importance of interaction as considerable factor in the teaching-learning process. Later, analyzing the production of records related to the game highlights the existence of a number of capabilities that could be developed or improved through the construction of representations records. Thus, it is considered that the use of games helps in the teaching and learning content for the Information Treatment block, and contribute to the development of understanding of mathematical representations capabilities.